Peran Stakeholder dalam Pengelolaan Kawasan Taman Wisata Alam Kawah Ijen - Wahyuningtiyas, Loetvy; Iskandar, Doddy Aditya (P4W IPB, 2023)
Ijen Crater Nature Park (TWAKI) is one of East Java Province's tourism destinations designated as a national tourism strategic area (KSPN). The natural beauty and the phenomenon of blue fire from the Ijen crater are an attraction for local and foreign tourists to visit the area. Also, an area that is prone to volcanic eruptions and fires. Administratively, Ijen is located in two districts, namely Banyuwangi and Bondowoso. The management of the area is carried out by the East Java Natural Resources Conservation Center (BBKSDA). Ijen borders the forest area managed by KPH Bondowoso and KPH Banyuwangi Barat. This potential area is also an attraction for stakeholders to be involved in developing Ijen Crater's natural tourism by their respective authorities. This study identifies the stakeholders' role in developing the TWAKI. The method used is an exploratory case study with pattern-matching analysis techniques. The study's results, namely the stakeholders' role in managing Ijen crater natural tourism, are divided into four categories: policy creators, implementers, facilitators, and conservators.